PERLINDUNGAN HUKUM DATA PRIBADI DALAM PERJANJIAN PINJAMAN ONLINE: Legal Protection of Personal Data in Online Loan Agreements - Alvina Rahim; Hetty Hassanah (Fakultas Hukum Universitas Komputer Indonesia, 2026)
In online loan transactions, the consent of a third party as the owner of the contact details is often required. This consent is crucial because it demonstrates that the third party is conscious of and accepts the possibility of a breach of contract by the borrower. However, borrowers often use other people's personal data to be listed as emergency loan contacts on the internet without the data owner's permission. Analyzing the type of legal protection for personal data is the aim of this study on emergency contacts listed unilaterally in online loan agreements in accordance with